Socialization of Stunting and Demonstration of Making Complementary Food as a Form of Community Service by KUKETA UNRI Students in Koto Damai Village: Sosialisasi Stunting dan Demonstrasi Pembuatan MP-ASI Sebagai Bentuk Pengabdian Masyarakat Mahasiswa KUKETA UNRI di Desa Koto Damai - Yuliani Putri; Dirgak Pandiloan Nusantara; Faizah Nabila; Dini Faiza Rahayu Suwartoyo; Ine Safanah (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
Stunting or chronic malnutrition is a distinct form of growth failure. Stunting is a chronic abnormality in growth caused by long-standing nutritional deficiencies or chronic and recurrent infectious diseases. Therefore, raising awareness and community participation in addressing this issue is essential. The socialization of stunting involves various community groups, including village midwives, mother volunteers, and mothers themselves. The prevention of stunting is closely related to the proper preparation of Complementary Feeding (MP-ASI). The right MP-ASI is a crucial factor in preventing stunting in children. When we design and prepare nutrient-rich and balanced MP-ASI, we indirectly provide children with adequate nutrition for their optimal growth and development. The implementation method in the community engagement program in Koto Damai Village regarding stunting prevention involves providing socialization and demonstrating the preparation of Complementary Feeding (MP-ASI) for mothers with infants and toddlers in Koto Damai Village. The series of socialization activities begins with the health examination of toddlers by the Integrated Health Post (Posyandu) team, followed by Stunting Prevention Socialization conducted by members of KUKERTA UNRI in collaboration with mother volunteers, with the hope of increasing community awareness and knowledge about stunting. Lastly, there is a demonstration of MP-ASI preparation designed to educate mothers on how to provide healthy and nutritious food for their infants and toddlers. The conclusion of this activity is that the prevention and management of stunting are crucial for a better future generation. Through stunting socialization and MP-ASI preparation demonstrations, it is hoped that a better generation can be realized and that community awareness and sensitivity regarding the importance of understanding stunting can be increased.